Conflits et identité en Valgrisenche - Alessandro Celi (Revue de Géographie Alpine)
Although Valgrisenche, a side valley of the Aosta Valley, is considered to be a poor and isolated valley consisting of stones and rocks, its inhabitants are widely known to have considerable wealth. This contradiction is due to the historical trials and tribulations of the area. In particular, the presence of the Col du Mont, which provided easy passage to Tarentaise, encouraged the development of trade that, during the Middle Ages, granted the valley a measure of wealth. By contrast, numerous conflicts since the 16th century caused the progressive closure of Valgrisenche. The valley became an important military target because of its location, which allowed invaders from France to avoid the bottleneck of the Pierre Taillée that encloses the upper part of the Aosta Valley. This article highlights the times of closure and describes the fortifications that marked the different historical periods. In particular, it demonstrates how the decisions of the War Department, which for 50 years prevented the construction of a motor road, led to a delay in the tourist development of Valgrisenche.